Expression of Concern: Rahman et al. An Overview of Antimicrobial Stewardship Optimization: The Use of Antibiotics in Humans and Animals to Prevent Resistance. Antibiotics 2022, 11, 667 - Antibiotics Editorial Office (MDPI AG, 2024)
With this notice, the Antibiotics Editorial Office states its awareness of concerns relating to the originality of the concepts and analysis published in this review [...]